Intersection of Literature, Culture and Education in Multidisciplinary Contexts - Chisunum, Jeffery; Anyima, Friday Fidelis (Media Publikasi Cendekia Indonesia, 2025)
Amid growing demands for graduates who can navigate the complexities of the twenty-first century, this study explores how integrating literature, culture, and education can reshape undergraduate learning. Drawing on constructivist learning theory, culturally responsive pedagogy, and interdisciplinary frameworks, the research responds to long-standing disciplinary divides that often hinder holistic development. Using a convergent parallel mixed-methods design, the study engaged 384 undergraduates at the University of Delta, Agbor, Nigeria, from January to June 2025. Three guiding aims structured the inquiry: understanding students’ initial interdisciplinary competencies, evaluating the influence of integrated pedagogical interventions, and exploring how culturally responsive teaching enhances learning. The results were compelling. Students exposed to the integrated approach demonstrated notable gains, including marked improvements in interdisciplinary thinking, academic performance, and cultural awareness. Statistical analyses confirmed the strength of these effects, with integrated methods accounting for over half of the variance in academic performance and culturally responsive pedagogy outperforming traditional teaching. Overall, these findings illustrate how deliberately weaving literature, culture, and education can create learning environments that are not only academically rigorous but also culturally meaningful. The study offers practical and theoretical insights for institutions seeking to prepare culturally aware, interdisciplinary thinkers equipped for a rapidly evolving world.